Age-related testosterone decline is due to waning of both testicular and hypothalamic-pituitary function. (3rd July 2015) - Golan, Ron; Scovell, Jason M.; Ramasamy, Ranjith
Abstract: Hypogonadism is a condition in which the endogenous secretion of testosterone is either insufficient or inadequate to maintain serum testosterone levels within normal range, and may manifest as a variety of signs and symptoms. Age-related hypogonadism is due to a combination of primary hypogonadism (testicular failure) and secondary hypogonadism (hypothalamic-pituitary axis failure). This review provides insight into the mechanisms resulting in the multifactorial nature of acquired androgen-deficiency, and outlines the current controversy regarding testosterone-replacement therapy in aging males.